Changes in retinal microvasculature and retinal layer thickness in association with apolipoprotein E genotype in Alzheimer’s disease - Joo Youn Shin (Nature Portfolio, 2021)
Abstract Biomarker tests of Alzheimer’s disease (AD) are invasive and expensive. Recent developments in optical coherence tomography (OCT) and OCT angiography (OCTA) have enabled noninvasive, cost-effective characterization of retinal layer vasculature and thickness. Using OCTA and OCT, we characterized retinal microvascular changes in the mild cognitive impairment (MCI) stage of AD and assessed their correlation with structural changes in each retinal neuronal layer. We also evaluated the effect of the APOE-ε4 genotype on retinal microvasculature and layer thickness. Retinal layer thickness did not differ between MCI patients (40 eyes) and controls (37 eyes, all p > 0.05). MCI patients had lower vessel density (VD) (p = 0.003) of the superficial capillary plexus (SCP) and larger foveal avascular zone area (p = 0.01) of the deep capillary plexus (DCP) than those of controls. VD of the SCP correlated with the ganglion cell layer (r = 0.358, p = 0.03) and inner plexiform layer thickness (r = 0.437, p = 0.007) in MCI patients. APOE-ε4-carrying MCI patients had a lower VD of the DCP than non-carriers (p = 0.03). In conclusion, retinal microvasculature was reduced in patients with AD-associated MCI, but retinal thickness was not changed; these changes might be affected by the APOE genotype. OCTA of the retinal microvasculature may be useful to detect vascular changes in AD.